Spectroscopic observations of merging galaxies - Donzelli, Carlos J. (2000)
In this paper we describe the spectroscopic and infrared properties of a sample of 25 merging galaxy pairs, selected from the catalog of Arp & Madore, and we compare them with those observed in a similar sample of interacting galaxies (Donzelli & Pastoriza). It is noted that mergers as well as interacting systems comprise a wide range of spectral types, going from those corresponding to well-evolved stellar populations (older than 200 Myr) to those that show clear signatures of H II regions with stellar populations younger than 8 Myr. However, merger galaxies show on average more excited spectra than interacting pairs, which could be attributed to lower gas metallicity. From the emission lines we also found that merging systems show on average higher (about a factor of 2) star formation rates than interacting galaxies. Classical diagnostic diagrams show that only three of 50 of the galaxies (6%) present some form of nuclear activity : two Seyfert galaxies and one LINER. However, through a detailed analysis of the pure emission-line spectra, we conclude that this fraction may raise up to 23% of the mergers if we consider that some galaxies host a low-luminosity active nucleus surrounded by strong star-forming regions. This latter assumption is also supported by the infrared colors of the galaxies. Regarding to the total infrared luminosities, the merging galaxies show on average an IR luminosity, log (Lir) lower than that of interacting systems log (Lir)=10.9. We find that only three mergers of the sample (12%) can be classified as luminous infrared galaxies, while this fraction increases to 24% in the interacting sample.